15. SEXUAL DYSFUNCTION IN KLINEFELTER'S SYNDROME PATIENTS IN ANDROLOGY AND FERTILITY HOSPITAL OF HANOI IN 2023-2024 (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate of sexual activity and function in Klinefelter’s syndrome patients in Andrology and Fertility Hospital of Hanoi and some related factors in 2023-2024. Methods: A cross-sectional study was conducted on 70 males with Klinefelter syndrome in the Andrology and Fertility Hospital of Hanoi Janury 2023 to March 2024. Evaluating erectile dysfunction through the scale (IIEF-5), premature ejaculation diagnostic tool (PEDT), intravaginal ejaculation latency time (IELT). Results: The mean age patients were 32.6 ± 4.2 years. The rate of erectile dysfunction was 22.9%, the IIEF-5 erectile dysfunction score was 23.21 ± 1.95. The rate of erectile dysfunction was higher in patients over 30 years old and in patients with overweight and obesity, p < 0,05. The rate of premature ejaculation was 31.4%, the average waiting time for ejaculation in the vagina was 6.97 ± 6.02 minutes, the shortest was 1 minute, the longest was 30 minutes. PEDT premature ejaculation score was 7.71 ± 2.56 points. Conclusion: The rate of erectile dysfunction and premature ejaculation in the KS group seem to be comparable with the data of the general population. Two contributing factors to elevated risk of erectile dysfunction are older age group (over 30 years old), overweight and obesity. Hopefully, there will be more research evaluating sexual function in KS men, contributing to creating a comprehensive basis for consultation and treatment, enhancing the quality of life for Klinefelter patients.
Keywords: Sexual dysfunction, sexual activity, Klinefelter’s syndrome.